The Digestive Tract of Cephalopods: Toward Non-invasive In vivo Monitoring of Its Physiology - Ponte, Giovanna; Sykes, Antonio V.; Cooke, Gavan M.; Almansa, Eduardo; Andrews, Paul L. R. (Frontiers in Physiology, 2017)
Ensuring the health and welfare of animals in research is paramount, and the normal functioning of the digestive tract is essential for both. Here we critically assess non- or minimally-invasive techniques which may be used to assess a cephalopod’s digestive tract functionality to inform health monitoring. We focus on: i. predatory response as an indication of appetitive drive; ii. body weight assessment and interpretation of deviations (e.g., digestive gland weigh loss is disproportionate to body weight loss in starvation); iii. oro-anal transit time requiring novel, standardised techniques to facilitate comparative studies of species and diets; iv. defaecation frequency and analysis of faecal colour (diet dependent) and composition (parasites, biomarkers and cytology); v. digestive tract endoscopy, but passage of the oesophagus through the brain is a technical challenge; vi. high resolution ultrasound that offers the possibility of imaging the morphology of the digestive tract (e.g., food distribution, indigestible residues, obstruction) and recording contractile activity; vii. needle biopsy (with ultrasound guidance) as a technique for investigating digestive gland biochemistry and pathology without the death of the animal. These techniques will inform the development of physiologically based assessments of health and the impact of experimental procedures. Although intended for use in the laboratory they are equally applicable to cephalopods in public display and aquaculture.